American Corrections System Response to COVID-19: an Examination of the Procedures and Policies Used in Spring 2020 - Marcum, Catherine D. (American journal of criminal justice, 2020)
This article will explore the federal and state correction system responses to COVID-19 as of early May 2020. Current statistics of infection rates and policy responses will be discussed. In addition, adjustments to inmate activities and staff will be reviewed, as well as responses by community corrections agencies.